2011
DOI: 10.1111/j.1741-6612.2010.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of educational interventions to prevent delirium

Abstract: The aim of this study was to combine knowledge about how clinicians learn with a review of educational interventions to prevent delirium in hospitalised patients. The primary aim was to evaluate the effectiveness of approaches to delirium education. A detailed search of educational and medical databases was undertaken. The type of intervention used was classified according to the PRECEED model of Green and colleagues, using factors relevant to behaviour change in health promotion. The effectiveness of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Most Type 1 studies did not report clinical performance and patient care outcomes but reported improved knowledge and self‐confidence in recognizing delirium, except two that reported improved recognition of delirium and behavior modification . Expectations for measurable effect on clinical outcomes in these studies is low, with the literature showing that isolated educational interventions involving predisposing factors alone are not effective in improving healthcare outcomes or changing provider behavior …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Most Type 1 studies did not report clinical performance and patient care outcomes but reported improved knowledge and self‐confidence in recognizing delirium, except two that reported improved recognition of delirium and behavior modification . Expectations for measurable effect on clinical outcomes in these studies is low, with the literature showing that isolated educational interventions involving predisposing factors alone are not effective in improving healthcare outcomes or changing provider behavior …”
Section: Discussionmentioning
confidence: 94%
“…An adaptation of the PRECEDE model was used to study the effectiveness of continuing medical education for physicians, but it is not known whether the same classification can be applied to most of the studies in this review that focus on interventions for nurses and allied health professionals. This point is significant because most of the interventions focused on nonphysician professionals, but use of the PRECEDE model has strong precedent in this type of review and provides an effective framework for characterizing educational interventions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Change in healthcare practice is challenging and requires complex, multi-modal educational strategies combining predisposing, enabling and reinforcing factors. 19,20 Predisposing factors include disseminating information, communication and didactic teaching. Enabling factors facilitate the desired change in performance by using protocols, guidelines and providing resources.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies that have been reported, results generally indicate that, while education can improve knowledge of dementia [13, 16], and delirium [17], education in isolation has little effect on clinical practice [18]. By comparison, the use of knowledge translation principles has been shown to be more effective in producing practice change and preventing delirium [10, 18, 19], and are recommended [20, 21]. …”
Section: Introductionmentioning
confidence: 99%